Late prehistoric coastal settlement patterns in the Cantabrian region, northern Spain - Rios-Garaizar, Joseba (2019)
Newly discovered archaeological sites in the Uribe Kosta region of northern Spain are illuminating the establishment of late prehistoric coastal farming settlements and specialised tool-production activities.